2016
DOI: 10.1371/journal.ppat.1005754
|View full text |Cite
|
Sign up to set email alerts
|

RIG-I Signaling Is Critical for Efficient Polyfunctional T Cell Responses during Influenza Virus Infection

Abstract: Retinoic acid inducible gene-I (RIG-I) is an innate RNA sensor that recognizes the influenza A virus (IAV) RNA genome and activates antiviral host responses. Here, we demonstrate that RIG-I signaling plays a crucial role in restricting IAV tropism and regulating host immune responses. Mice deficient in the RIG-I-MAVS pathway show defects in migratory dendritic cell (DC) activation, viral antigen presentation, and priming of CD8+ and CD4+ T cell responses during IAV infection. These defects result in decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…Instead, it appears that the inclusion of the isRNA innate immune agonist had the greatest influence on vaccine immunogenicity. Despite the importance of RIG-I signaling in generating antigen-specific T cells, 34 we did not measure a significant increase in the numbers of IFN-g + or IL-2 + T cells for either antigen. This is in agreement with previous findings that the isRNA expression did not enrich T cell immunity, possibly due to the lack of a hairpin structure in the dsRNA transcribed from the Nanoplasmids.…”
Section: Discussionmentioning
confidence: 62%
“…Instead, it appears that the inclusion of the isRNA innate immune agonist had the greatest influence on vaccine immunogenicity. Despite the importance of RIG-I signaling in generating antigen-specific T cells, 34 we did not measure a significant increase in the numbers of IFN-g + or IL-2 + T cells for either antigen. This is in agreement with previous findings that the isRNA expression did not enrich T cell immunity, possibly due to the lack of a hairpin structure in the dsRNA transcribed from the Nanoplasmids.…”
Section: Discussionmentioning
confidence: 62%
“…RIG‐I is an innate sensor and direct antiviral factor against IAV infection. Inhibition of RIG‐I certainly impairs type I IFN production, immune cell activation and stimulation of the adaptive immune system . These results suggest that IAV‐induced MCPIP1 is not only involved in antiviral effects, but in controlling RIG‐I signaling, which is beneficial to the virus at later times of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Within the cytosol of IAV‐infected epithelial cells, RIG‐I recognizes and binds to the 5′‐triphosphate with blunt‐ended double‐stranded RNA component as contained in panhandle of the IAV genome, which then binds to its downstream adaptor molecule mitochondrial antiviral signaling protein (MAVS) . Upon its activation, RIG‐I/MAVS induces the activation of transcription factor interferon (IFN) regulatory factor (IRF) 3 and NF‐κB, ultimately resulting in establishing an antiviral state against IAV in the host cells through both type I IFN production and efficient polyfunctional T cell responses …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that multifunctional cellular immune responses might be involved in the self‐cure process. Several studies have demonstrated the protective roles of host polyfunctional cells against numerous infectious organisms . For example, the frequency of Plasmodium falciparium ‐specific polyfunctional T cells has been associated with protection in humans .…”
Section: Discussionmentioning
confidence: 99%